Win, lose, or draw?: China’s quarter century war on corruption - Wedeman, Andrew Hall (Crime, law and social change, 2008)
In 1982, the leadership of the Chinese Communist Party ordered a crackdown on corruption. As China’s war on corruption enters its 25 year an obvious question is whether the party winning? Because there is no direct way to measure the actual rate of corruption (ARC) and the data we have on the revealed rate of corruption (RRC) may not perfectly reflect changes in the ARC while changes in the perceived level of corruption (PLC) may be subject to subjective distortion, trends in the RRC and the PLC may not provide reliable answers. The mathematical relationship between the ARC and the RRC, however, can be defined as a function of risk. Increases in risk can be interpreted as signaling a narrowing of the ARC-RRC gap. Decreases in risk can be interpreted as signaling a widening of the ARC-RRC gap. By combining data on changes in risk with data on movement in the RRC it is possible, therefore, to assess (in broad terms) the movement of the ARC even though it remains technically unknowable. Using data on the lag between when officials first engage in corruption and when they are prosecuted to measure changes in risk, this article raises doubts about whether Chinese Communist Party (CCP) is winning its war on corruption.